Circadian Biology and Stroke. Issue 6 (4th May 2021) - Lo, Eng H.; Albers, Gregory W.; Dichgans, Martin; Donnan, Geoffrey; Esposito, Elga; Foster, Russell; Howells, David W.; Huang, Yi-Ge; Ji, Xunming; Klerman, Elizabeth B.; Lee, Sarah; Li, Wenlu; et al.
Abstract : Circadian biology modulates almost all aspects of mammalian physiology, disease, and response to therapies. Emerging data suggest that circadian biology may significantly affect the mechanisms of susceptibility, injury, recovery, and the response to therapy in stroke. In this review/perspective, we survey the accumulating literature and attempt to connect molecular, cellular, and physiological pathways in circadian biology to clinical consequences in stroke. Accounting for the complex and multifactorial effects of circadian rhythm may improve translational opportunities for stroke diagnostics and therapeutics.